Peran Unit Pelayanan Perempuan Dan Anak Dalam Menangani Kasus Pemerkosaan Yang Melibatkan Anak Sesuai Dengan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak - Muhammad Roihan; Ceppy Sukma Asmara; Ragil Mauladian; Igen Opawiranda; Liza Deshaini (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
One of the institutions that has an important role in handling cases of violence against women and children, including rape cases, is the Women and Children's Service Unit which is under the auspices of the Republic of Indonesia National Police. How is the Role of the Women and Children's Service Unit in Handling Rape Cases Involving Children in Accordance with Law Number 35 of 2014 concerning Child Protection? The research method used is the type of research and normative legal approach. The role of the Women and Children's Service Unit in providing legal protection to rape victims in accordance with Law Number 35 of 2014 concerning Child Protection is to encourage victims to participate in the investigation and prosecution process through regulations / procedures that create a sense of physical and psychological security, reduce trauma experienced by victims, protect victims from violence and retaliatory attacks from the perpetrator or the perpetrator's family, resulting in punishment for those guilty of committing crimes. Recommendations, the Women and Children's Service Unit needs to build a stronger network of cooperation with related agencies, such as the Integrated Service Center for the Empowerment of Women and Children (P2TP2A), social services, and hospitals.